PEMANTAUAN NARAPIDANA ASIMILASI PADA MASA PANDEMI COVID-19 DI BALAI PEMASYARAKATAN KELAS 1 PALEMBANG - Farhan Akbar Mu'arif (Al Qisthas: Jurnal Hukum dan Politik Ketatanegaraan, 2022)
This study took the locus of the Class 1 Palembang Fathers with a focus on the problem of maintaining assimilation prisoners during the COVID-19 pandemic. OverCrowding Prisoners in most of the Correctional Units are afraid that the inmates will not be able to carry out social distancing in accordance with health protocols which can increase the vulnerability of the transmission of the Covid-19 virus. The Ministry of Law and Human Rights of the Republic of Indonesia issued a regulation on the issue of covid-19 to stop the transmission of COVID-19. The regulation is the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Prevention and Control of the Spread of Covid-19. This study concludes that rapid treatment must be carried out so that this viral chain ends soon.